Immunometabolic profiling of cervicovaginal lavages identifies key signatures associated with adenomyosis - Georgia M. Lorentzen; Paweł Łaniewski; Haiyan Cui; Denise J. Roe; Jamal Mourad; Nichole D. Mahnert; Leslie V. Farland; Melissa M. Herbst-Kralovetz (iScience, 2022)
Summary: Adenomyosis is a burdensome gynecologic condition that is associated with pelvic pain, dysmenorrhea, and abnormal uterine bleeding, leading to a negative impact on quality of life; and yet is often left undiagnosed. We recruited 108 women undergoing hysterectomy for benign gynecologic conditions and collected non-invasive cervicovaginal lavage samples for immunometabolic profiling. Patients were grouped according to adenomyosis status. We investigated the levels of 72 soluble immune proteins and >900 metabolites using multiplex immunoassays and an untargeted global metabolomics platform. There were statistically significant alterations in the levels of several immune proteins and a large quantity of metabolites, particularly cytokines related to type II immunity and amino acids, respectively. Enrichment analysis revealed that pyrimidine metabolism, carnitine synthesis, and histidine/histamine metabolism were significantly upregulated pathways in adenomyosis. This study demonstrates utility of non-invasive sampling combined with immunometabolic profiling for adenomyosis detection and a greater pathophysiological understanding of this enigmatic condition.